Position of the victim's right at the pre-trial stage: a comparative study between the Iranian and Malaysian criminal proceeding law / Mehran Farahmand ... [et al.] - Farahmand, Mehran; Abdul Rahim, Anita; Tegku Zainudin, Tengku Noor Azira (2014)
In most common law countries the public prosecutor will act on behalf of the state in prosecuting the case. In a criminal proceeding, there are only two parties involved; the prosecutor and the accused. As opposed to the common law system, the Iranian law practises a different system whereby the victim has many rights in a criminal proceeding given by the provisions of law. Iranian crimes divided into three main division, sharia‟ laws, public discipline and individual rights. This category give many rights to the victim in criminal process that have many effect in criminal process. With these rights victim can apply something different in criminal cases and in most of times the court should accept his request. Victim rights will apply in all steps of trial and in crime with private aspect can suspended the trial and also in crimes with public aspect can be effective in all stages. These rights considers a harmful right in proceeding that can to affect the justice